DEVELOPMENT OF INTERACTIVE E-MODULES ON DRAWING FEMALE BODY ANATOMY COMPARISON OF 11xHEAD HEIGHT IN CLASS X - Nur Amelia Sari; Agusti Efi (Gorga : Jurnal Seni Rupa, 2024)
Students of SMK Negeri 3 Kota Solok have difficulty learning the basics of fashion learning material on drawing body anatomy as a basis for designing clothes. Therefore, the development of interactive e-modules aims to be an alternative means to help in learning the basics of fashion. This study uses a 4D (four D) development model, consisting of Define, Design, Development, and Disseminate, and this study was only carried out up to the development stage. The data collected from this study are data analysis of media validity tests and practicality tests. Based on the results of the study, it can be concluded that the e-module of anatomical drawings for fashion students that was developed is valid and practical, thus the interactive e-module of the material on drawing the anatomy of a woman's body with a ratio of 11xhead height is suitable for use as a learning medium at SMK Negeri 3 Kota Solok.